Fungsi Manajemen Kepala Sekolah dalam Implementasi Pendidikan Inklusi untuk Mewujudkan Sekolah Ramah Anak di Sekolah Dasar - Pramesti Dewi; Ghufron Abdullah; Lilik Ariyanto (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to analyze the principal’s management functions in the implementation of inclusive education to create a child-friendly school in elementary school. The method used was a descriptive qualitative approach conducted at SD Negeri 2 Jangkungharjo, Grobogan Regency. The research subjects consisted of the principal and classroom teachers. Data collection techniques included interviews, observations, and documentation. Data analysis employed an interactive model consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results showed that the principal had implemented management functions, including planning, organizing, directing, and controlling, systematically in supporting inclusive education. In conclusion, the principal’s management functions play an important role in creating an inclusive, safe, and non-discriminatory school environment despite limited resources. Keywords: Management Functions, Principal, Inclusive Education, Child-Friendly School